2021
DOI: 10.1186/s13073-021-00900-3
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlations and novel molecular insights into the DHX30-associated neurodevelopmental disorders

Abstract: Background We aimed to define the clinical and variant spectrum and to provide novel molecular insights into the DHX30-associated neurodevelopmental disorder. Methods Clinical and genetic data from affected individuals were collected through Facebook-based family support group, GeneMatcher, and our network of collaborators. We investigated the impact of novel missense variants with respect to ATPase and helicase activity, stress granule (SG) format… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 48 publications
(84 reference statements)
3
28
0
Order By: Relevance
“…The authors further used cell culture and zebrafish models to demonstrate that endogenous DHX30 leads to stress granule aggregation under heat stress conditions, while DHX30 deletion contributes to a reduction in the number of stress granules in these models. In addition, behavioral assessment of DHX30 knockouts in zebrafish showed altered sleep-wake behavior, which is consistent with patterns of sleep disturbance observed in several individuals carrying DHX30 variants [ 1 ].…”
Section: Molecular Subtypes and Functional Convergencesupporting
confidence: 67%
See 4 more Smart Citations
“…The authors further used cell culture and zebrafish models to demonstrate that endogenous DHX30 leads to stress granule aggregation under heat stress conditions, while DHX30 deletion contributes to a reduction in the number of stress granules in these models. In addition, behavioral assessment of DHX30 knockouts in zebrafish showed altered sleep-wake behavior, which is consistent with patterns of sleep disturbance observed in several individuals carrying DHX30 variants [ 1 ].…”
Section: Molecular Subtypes and Functional Convergencesupporting
confidence: 67%
“…For instance, loss-of-function variants, such as frameshift and nonsense mutations or whole gene deletions, only resulted in milder phenotypes, suggesting distinct effects on protein function due to missense variants in specific locations. Although in vitro experiments did not paint a clear picture, overall trends suggested that missense mutations led to a significant loss of ATPase and helicase activity, reduction in global translation, and formation of stress granules [ 1 ].…”
Section: Allelic Heterogeneity: Another Layer Of Complexitymentioning
confidence: 99%
See 3 more Smart Citations